High-affinity caspase-4 binding to LPS presented as high molecular mass aggregates or in outer membrane vesicles - Wacker, Mark A (Innate Immun, 2017)
Caspases of the non-canonical inflammasome (caspases-4/5/11) directly bind endotoxin (LOS/LPS) and can be activated in the absence of any co-factors. Models of LPS-induced caspase activation have postulated that 1:1 binding of endotoxin monomers to caspase trigger caspase oligomerization and activation, analogous to that established for endotoxin-induced activation of MD-2/TLR4. However, using metabolically radiolabeled LOS and LPS, we now show high affinity and selective binding of caspase-4 to high molecular-mass aggregates of purified endotoxin and to endotoxin-rich outer membrane vesicles without formation of 1:1 endotoxin:caspase complexes. Our findings thus demonstrate markedly different endotoxin recognition properties of caspase-4 from that of MD-2/TLR4 and strongly suggest that activation of caspase-4 (and presumably -5 and -11) are mediated by interactions with activating endotoxin-rich membrane interfaces rather than by endotoxin monomers.